Thermo-Electro-Fluidic Simulation Study of Impact of Blower Motor Heat on Performance of Peltier Cooler for Protective Clothing - Kwon Joong Son (Energies, 2023)
The necessity for portable cooling devices to prevent thermal-related diseases in workers wearing protective clothing in hot outdoor weather conditions, such as COVID-19 quarantine sites, is increasing. Coolers for such purposes require a compact design and low-power consumption characteristics to maximize wearability and operating time. Therefore, a thermoelectric device based on the Peltier effect has been widely used rather than a relatively bulky system based on a refrigeration cycle accompanying the phase change of a refrigerant. Despite a number of previous experimental and numerical studies on the Peltier cooling device, there remains much research to be conducted on the effect and removal of motor-related internal heat sources deteriorating the cooling performance. Specifically, this paper presents thermo-electro-fluidic simulations on the impact of heat from an air blower on the coefficient of performance of a Peltier cooler. In addition, a numerical study on the outcome of heat source removal is also evaluated and discussed to draw an improved design of the cooler in terms of cooling capacity and coefficient of performance. The simulation results predicted that the coefficient of performance could be raised by 10.6% due to the suppression of heat generation from a blower motor. Accordingly, the cooling capacity of the specific Peltier cooler investigated in this study was expected to be considerably improved by 80.6% from 4.68 W to 8.45 W through the design change.